Performa produksi dan kualitas susu sapi perah pada masa pandemi penyakit mulut dan kuku di tempat pelayanan Koperasi KPBS Pangalengan yang menerapkan milk collection point - Febrianto Christi, Raden; Hermawan; Farkhan, Anindya (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2024)
Foot-and-mouth disease (FMD) is an infectious disease that can affect dairy cows, leading to mortality and a decrease in milk production. This study aims to examine the production and quality of milk from dairy cows at Service Cooperative Points (SCP) implementing the Milk Collection Point (MCP) system in the Bandung Selatan Livestock Cooperative, Pangalengan, during the FMD pandemic. The research employed a census method analyzed using descriptive quantitative techniques. The results showed that the highest decrease in milk production occurred in July, with 7.2% at SCP Mekar Mulya and 47.58% at SCP Los Cimaung. This reduction was attributed to cow mortality, forced slaughter, and the impact of lactating cows contracting FMD. Subsequently, milk production increased in the following months, with the highest increase during the FMD pandemic recorded at 13.16% at SCP Mekar Mulya and 27.31% at SCP Los Cimaung. By August, milk production showed a consistent increase and stabilized through September. Additionally, milk quality during the FMD pandemic continued to meet the Indonesian National Standard (SNI). However, the resazurin grade dropped by one level compared to the pre-pandemic period. It can be concluded that the FMD outbreak caused a significant decrease in dairy cow milk production in SCP that implemented MCP at KPBS Pangalengan but did not reduce milk quality. There was an increase in fat, which was suspected to be due to a decrease in the amount of production and a decrease in resazurin grade by one level compared to before the pandemic.